Automated manufacture of 3D reinforced aerospace composite structures - Dell'Anno, Giuseppe; Partridge, Ivana K.; Cartié, Denis D. R.; Hamlyn, A.; Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (Cranfield University, 2012)
Purpose- This study is part of the FP7 project ADVITAC and focuses on exploring an innovative combination of cutting edge technologies to be implemented within automated processes for composite parts manufacturing. The objective is the design of a production route for components with tailored fibre orientation and ply lay-up, with improved damage tolerance thanks to through-the-thickness reinforcement and integrated health monitoring systems based on optical fibres technology. Design/Methodology/Approach- The proposed technologies are described in detail and their compatibility and potential for integration are discussed. A set up for on-line monitoring of infusion and curing processes of carbon/epoxy laminates preformed by dry fibre placement technology is proposed, and a preliminary study of their mechanical performance is presented. The possibility of reinforcing through-the-thickness preforms manufactured with dry slit tapes automatically laid-up and consolidated by laser heating is investigated. Findings- Improved knowledge of interaction/compatibility between the discussed technologies and scope for application. Research limitations/implications- The paper reports the technical potential and practical feasibility of the proposed integrated production process. Limited quantitative evaluations on the materials performance are provided. The analysis of the technologies involved represents the early outcome of the ongoing ADVITAC project. Practical implications- This study contributes to the identification of a new generation of composite architecture which allows production cost and weight savings while retaining the level of quality suitable for demanding structural applications, with particular relevance to the aerospace field. Originality/value- This paper investigates for the first time the practical possibility of designing a single automated process involving dry fibre placement, tufting and optical fibre sensor monitoring for the production of complex composite components.
Keywords: automation, manufacturing, tufting, robot, cure monitoring, optical fibre sensor